2020
DOI: 10.1111/bre.12442
|View full text |Cite
|
Sign up to set email alerts
|

Predicting sediment discharges and erosion rates in deep time—examples from the late Cretaceous North American continent

Abstract: Depositional stratigraphy represents the only physical archive of palaeo-sediment routing and this limits analysis of ancient source-to-sink systems in both space and time. Here, we use palaeo-digital elevation models (palaeoDEMs; based on highresolution palaeogeographic reconstructions), HadCM3L general circulation model climate data and the BQART suspended sediment discharge model to demonstrate a predictive, forward approach to palaeo-sediment routing system analysis. To exemplify our approach, we use palae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(43 citation statements)
references
References 150 publications
(273 reference statements)
0
43
0
Order By: Relevance
“…2019; Lyster et al . 2020), increasing the likelihood of fossil preservation. In contrast, whilst several transgressive marine tongues are observed within the Hell Creek formation (Fastovsky & Bercovici 2016), the Maastrichtian overall saw a retreat of the WIS, with possible east–west land connection between the two North American subcontinents (Slattery et al .…”
Section: Discussionmentioning
confidence: 99%
“…2019; Lyster et al . 2020), increasing the likelihood of fossil preservation. In contrast, whilst several transgressive marine tongues are observed within the Hell Creek formation (Fastovsky & Bercovici 2016), the Maastrichtian overall saw a retreat of the WIS, with possible east–west land connection between the two North American subcontinents (Slattery et al .…”
Section: Discussionmentioning
confidence: 99%
“…As such, these reconstruction tools are not appropriate, by themselves, for reconstructing the total sediment load of a wash load-dominated system, for example. Knowledge of prevailing sediment transport modes is important for evaluating whether different sediment discharge reconstruction methods are consistent with one another, as studies that reconstruct sediment discharges often corroborate results with an independent approach (Lin & Bhattacharya, 2017;Watkins et al, 2018;Zhang et al, 2018;Brewer et al, 2020;Lyster et al, 2020).…”
Section: (B) Planform Morphologiesmentioning
confidence: 99%
“…A key research challenge is to decode this archive to reconstruct the movement of water and sediment across Earth's surface in the geological past (Castelltort & Van Den Driessche, 2003;Jerolmack & Paola, 2010;Ganti et al, 2014;Romans et al, 2016;Straub et al, 2020) -effective quantification of palaeohydrology from fluvial stratigraphy is crucial to achieve this goal. Constraints on the morphologies and hydrodynamics of palaeorivers can be used to: resolve the size and scale of ancient catchments (Bhattacharya & Tye, 2004;Bhattacharya et al, 2016;Eide et al, 2018;Lyster et al, 2020); quantify sediment transport capacities and the magnitudes of sediment exported to oceans (Allen et al, 2013;Holbrook & Wanas, 2014;Lin & Bhattacharya, 2017;Sharma et al, 2017); decipher fluvial response to perturbation (Foreman et al, 2012;Foreman, 2014;Colombera et al, 2017;Chen et al, 2018); and reconstruct local palaeogeographies (Li et al, 2018). Importantly, these constraints can be used to investigate hydrological response to long-period forcing (>10 6 yrs) as river behaviour is intrinsically linked to tectono-climatic boundary conditions over geological timescales (Duller et al, 2010;Whitchurch et al, 2011;Whittaker et al, 2011;Castelltort et al, 2012;.…”
mentioning
confidence: 99%
“…The advantage of using Equation ( 5) is that the full possible range in water discharge for each climate zone is captured as opposed to a single averaged value (Table 2). Alternatively, paleoclimate modelling (e.g., Armstrong et al, 2016;Jacob et al, 2001;Sellwood & Valdes, 2008) can provide a useful tool to reconstruct the catchment-wide climate conditions, including precipitation, to define paleo-water discharge for the Q parameter as demonstrated recently by Lyster et al (2020).…”
Section: Water Discharge (Q)mentioning
confidence: 99%
“…Helland-Hansen et al (2016) notes that the approach does not capture the low-frequency, high-amplitude events which may dominate a significant portion of sediment transport and deposition on geological timescales. In addition, the method does not account for bedload material and appears more sensitive to uncertainty in temperature of cooler climates (Lyster et al, 2020). Analytically, catchment area is the largest potential source of uncertainty ranging five orders of magnitude (Eide, Klausen, et al, 2018) and combined with estimation of catchment relief is suggested to be the largest uncertainty in the BQART model for ancient S2S studies (Brewer et al, 2020).…”
Section: Introductionmentioning
confidence: 99%